Republic of Tajikistan : Private Sector Development Strategy - World Bank (World Bank, Washington, DC, 2014)
This report sets out recommendations for the Government of Tajikistan to implement in order to make feasible its intention to develop a comprehensive strategy for private sector development. Many of these actions - such as eliminating restrictions on the term of licenses and reducing the number of licenses to 65 - can be accomplished in less than a year and should show rapid results, thus demonstrating the Government's credibility in conducting reforms and strengthening business and investor confidence that improvements in investment climate are now a reality. The study believes that in order to sustain economic growth over the medium and long-term, Tajikistan will clearly need to attract investment and further diversify its economy. Realizing this potential, however, will require significant improvements in its investment climate, not only through the continued modernization of its legal and regulatory framework, but the institutional capacity to implement the reforms they were intended to realize. Otherwise, the private sector in Tajikistan will continue to have to cope with an unclear and overly cumbersome regulatory and institutional framework that stifles competition, increases the cost and risk of doing business, and discourages innovation and risk taking.